Moving from food crisis to food security in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2011)
ACP countries must not only cope with the current food crisis and corresponding dramatic increases in food prices, but devise policies to ensure food security for future generations in the face of rapid population growth. In the Brussels Development Briefing on ‘The Geopolitics of Food’ experts agreed that there is no miracle solution to the world’s food crisis. Covering topics such as food security, economics and policy, this CTA Policy Brief highlights the need for a significant increase in investment in agricultural and rural development. It also highlights the need for policy-makers to promote intensive forms of green agriculture, strengthen smallholder farmers and farmers’ organisations, and improve food governance.